Measuring the Roles and Communication Patterns of School Committees in Improving School Quality on Basic Education Level in Yogyakarta - Yenni Sri Utami (The Indonesian Journal of Communication Studies, 2009)
The study deals with measuring the role and communication pattern of school committee in improving school quality on basic education level in Yogyakarta. School committee is an independent organization as a way for society to increase quality and efficiency of school management. It is an effort to realize school management based on society. Thus, the success of education is not merely the responsibility of central government, but also provincial government, school's bureaucracy, parents as well as society. Although the existence of school committee can motivate society to participate in education management, but due to relatively new, some distortions still occur. Therefore, the role of school committee is highly expected for society to participate in school management optimally. This phenomenon has been happened in many SD (primary schools in Yogyakarta city). This Research used qualitative methods with descriptive-qualitative approach. Non-participant observation and in-depth interview were used to collect the data. The study indicates that the school committees played roles as advisory, supporting, controlling, and mediating agencies at SDN Serayu, SDN Pujokusuman I, SDN Percobaan I and SD Muhammadiyah Sukonandi in Yogyakarta city. Nonetheless, the roles were still not optimized. It means that the role of school committee at these schools were still equal to BP3 model. The role of school committees were more focussed on the development of school. This condition is contrast to other school committees developed in SD Ungaran I and SD Muhammadiyah Sapen whose role and communication had run effectively. Keywords: school committee, school management, role and communication patterns